Analisis Pembelajaran PAI dengan Pendekatan Integratif dalam Kurikulum Merdeka - Ma’rifatul Nur; Khuriyah Khuriyah; Zahro Amirotun; Wisnu Agung (CV. ULIL ALBAB CORP, 2025)
The Independent Curriculum initiated by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia aims to create a learning process that is centered on students and relevant to the needs of the times. In the context of Islamic Religious Education, an integrative approach is one of the relevant strategic methods to align religious values with science and everyday life. This article analyzes the implementation of Islamic Religious Education learning with an integrative approach in the Independent Curriculum, identifies the challenges and opportunities faced, and provides recommendations for optimizing the learning process. The research method in this article is qualitative research using a literature review approach. The data obtained are then analyzed using the content analysis method to identify the main ideas from the various sources used. This study aims to explore how the application of an integrative approach in Islamic Religious Education learning in the Independent Curriculum. The advantages of the integrative approach are increasing understanding and relevance, building Islamic character, developing creativity and collaboration, and enriching insight. The challenges of implementation are limited teacher understanding, limited resources, the need for additional training, and limited time.